PERBEDAAN PERSEPSI KONSUMEN PADA ELEKTRONIK MEREK ASING DAN LOKAL - Fitantina, Fitantina; -, Anas (Jurnal Ilmu Manajemen, 2017)
The formulation of the problem in this research is whether there is differences ofconsumer perceptions on foreign and local electronic brands in Kenten Laut,Talang Kelapa Subdistrict, Banyuasin Regency, Palembang. The purpose ofthis research is to know the differences of consumer perceptions on foreignand local electronic brands in Kenten Laut, Talang Kelapa Subdistrict,Banyuasin Regency, Palembang. This study includes a comparative studycomparing one sample with another sampel, whereby this study aims todetermine differences in consumer perceptions on foreign and localelectronic brands in Kenten Laut, Talang Kelapa Subdistrict, BanyuasinRegency, Palembang. The population is all KK in Kenten laut. Sample in this research is 200 KK, with technique of closter sampling analysis. Types of data used are primery and secondary data. Data is collected by usingquestionnaire, with analysis tool using chi-square. The results of theresearch indicate that there are differences of consumer perceptions onforeign and local electronic brands in Kenten Laut, Talang KelapaSubdistrict, Banyuasin Regency, Palembang. The difference in the intent isfound in foreign and local electronic brand products.